Filsafat Ekonomi Musa Asy’arie - Muhdhori Ahmad; Aksin Wijaya; Khusniati Rofi’ah (Journal of Economics, Law, and Humanities, 2025)
This study examines in depth the economic philosophy of Musa Asy’arie, as formulated in the Islamic Economic Trilogy, comprising Economic Theology, Economic Cosmology, and Economic Anthropology. These ideas provide an ethical framework for modern economic practices by integrating divine values, cosmological balance, and a human-centered understanding. The purpose of this research is to explain the concept of Musa Asy’arie’s Islamic Economic Trilogy and assess its relevance to contemporary economic dynamics. This study employs library research with a qualitative method, based on textual data from books, scientific articles, and primary documents authored by Musa Asy’arie. Data were collected through a literature review and analyzed using content analysis with a deductive approach and a sociological perspective that positions humans as social beings within economic practice. The findings demonstrate that Musa Asy’arie’s Islamic Economic Trilogy makes a significant contribution to the development of economic ethics, providing a moral orientation for business activities, entrepreneurship, and growth. The concept emphasizes the importance of integrating tawhid values, cosmological balance, and anthropological understanding to build an economic system that is just, sustainable, and civilized. The study concludes that Musa Asy’arie’s economic thought remains highly relevant for further development and application in modern economic contexts, both as a theoretical foundation and as practical guidance for shaping ethical economic behavior.